2010
DOI: 10.1186/cc8929
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy during stagnant ischemia estimates central venous oxygen saturation and mixed venous oxygen saturation discrepancy in patients with severe left heart failure and additional sepsis/septic shock

Abstract: IntroductionDiscrepancies of 5-24% between superior vena cava oxygen saturation (ScvO2) and mixed venous oxygen saturation (SvO2) have been reported in patients with severe heart failure. Thenar muscle tissue oxygenation (StO2) measured with near-infrared spectroscopy (NIRS) during arterial occlusion testing decreases slower in sepsis/septic shock patients (lower StO2 deoxygenation rate). The StO2 deoxygenation rate is influenced by dobutamine. The aim of this study was to determine the relationship between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 29 publications
(44 reference statements)
0
24
0
Order By: Relevance
“…Some authors explored the correlation of StO 2 with parameters of global oxygenation, such as central venous oxygen saturation (ScvO 2 ) [5155], demonstrating that low StO 2 values (i.e., StO 2 < 75% when measured on the thenar eminence) specifically predict extremely low ScvO 2 values [15, 51, 52]. However, the sensitivity of StO 2 variables to detect these situations of global hypoperfusion is considerably low, and therefore the absolute StO 2 value has been proposed as an initial tool to rapidly and noninvasively detect hypoperfusion states, but only while other more sensitive variables are not available [23, 51, 52].…”
Section: Adding Sto2 To Current Resuscitation Algorithms?mentioning
confidence: 99%
“…Some authors explored the correlation of StO 2 with parameters of global oxygenation, such as central venous oxygen saturation (ScvO 2 ) [5155], demonstrating that low StO 2 values (i.e., StO 2 < 75% when measured on the thenar eminence) specifically predict extremely low ScvO 2 values [15, 51, 52]. However, the sensitivity of StO 2 variables to detect these situations of global hypoperfusion is considerably low, and therefore the absolute StO 2 value has been proposed as an initial tool to rapidly and noninvasively detect hypoperfusion states, but only while other more sensitive variables are not available [23, 51, 52].…”
Section: Adding Sto2 To Current Resuscitation Algorithms?mentioning
confidence: 99%
“…(57) The hypothesis that the slower skeletal muscle StO2 deoxygenation rate (more disturbed tissue oxygen extraction) is proportional to the ScvO2-SvO2 difference in patients with severe heart failure with additional sepsis/septic shock, was confirmed by our more recent study. (58) We showed that these patients had a clinically considerable ScvO2-SvO2 discrepancy. Monitoring ScvO2 is a simpler and cheaper assessment of global DO2 to oxygen consumption ratio, but its use as a treatment goal in patients with severe heart failure, with additional sepsis/septic shock, is questionable.…”
Section: Introductionmentioning
confidence: 68%
“…NIRS was introduced in the 1970s by Jöbsis2 to study cerebral and myocardial blood flow. The technique is currently used in clinical testing to investigate muscle,3 breast tumors,4, 5 cerebral tissue,6, 7 peripheral and cerebrovascular disease,8, 9 and congestive heart failure 10. The advantages of the NIRS technique are its non‐invasiveness, ease of application, and low signal–noise during exercise.…”
Section: Discussionmentioning
confidence: 99%